NOMINA BAHASA KAILI DIALEK RAI - Susanti, Ariska; Syamsuddin, Syamsuddin; Ulinsa, Ulinsa (BAHASANTODEA, 2017)
The research problems are: (1) how is the form of noun of Kaili language in Rai dialect?, (2) how is the function of noun of Kaili language in Rai dialect?, and (3) what is the meaning of noun of Kaili language in Rai dialect?. The research aims to: (1) describe the noun form of Kaili language in Rai dialect, (2) describe the noun function of Kaili language in Rai dialect, and (3) describe the meaning of noun of Kaili language in Rai dialect. This was a descriptive qualitative research. Data collection was listening and speaking with listening involving speaking, recording technique, and noting technique. Data analysis used match and distributional with subtitution technique. The research result reveals that (1) the form of the noun of Kaili language in Rai dialect includes the basic noun that is a noun consisting of a morpheme and a derived noun that is a derived noun with the form of the affix, reduplication, compounding, and clitization on the morphological study and noun of Kaili language in Rai dialect on the study of syntax can be known its position in construction of phrases, clauses, and sentences. (2) the Kaili language noun function in the Rai dialect includes the morphological noun function ie as a tool marker, locative adverb marker, and numerical marker. (3) the meaning of Kaili’s noun in Rai dialect in morphology and syntax is to have meaning as component of the meaning of people, animals, fruits, food, tools, place of people perfoming an activity or work, many or more than one, and meaningful to one.